Genes, the serotonergic system and suicidal behavior (2012)
The study of suicidal behavior has gained relevance given that recently about 50% of the population between 14 and 19 years old exhibit suicidal ideation and, in the population in general, there has been a rise of up to 150% in suicidal behavior. The outcomes of these studies of genetic epidemiology show that several genes may be associated with suicidal behavior. In particular, one of the hypotheses propounds that genes of proteins that participate in the serotonergic pathway could be responsible for the development of this behavior. There is neurochemical evidence showing alterations at different levels along this pathway. In this work, a review is made of several of the genes participating in the serotonergic pathway and their possible participation in suicidal behavior.